2021
DOI: 10.2991/assehr.k.210326.042
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Regarding Students’ Learning Motivation by Gender During the Online Learning

Abstract: This study's objectives were to investigate and analyze comparisons of students' learning motivation during online learning based on gender. This quantitative study used a survey design. The subject study consisted of 331 students in the high school selected from science majors using the convenience sampling technique. The Instrument was adopted by The Motivated Strategies Learning Questionnaire (MSLQ), which consisted of five aspects (self-efficacy, intrinsic value, test anxiety, strategy use, self-regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…According to the research table there is a significant difference in intrinsic motivation between boys and girls (Spinath, Eckert, & Steinmayr, 2018). Researchers measuring male and female students' learning motivation for online learning have found significant differences, with the mean score for female students' learning motivation being significantly higher than the mean score for male students' learning motivation (Puspitaningrum, Prodjosantoso, & Pulungan, 2021). Ramdani et al's study showed differences in thinking between boys and girls (Ramdani & Yustiqvar, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the research table there is a significant difference in intrinsic motivation between boys and girls (Spinath, Eckert, & Steinmayr, 2018). Researchers measuring male and female students' learning motivation for online learning have found significant differences, with the mean score for female students' learning motivation being significantly higher than the mean score for male students' learning motivation (Puspitaningrum, Prodjosantoso, & Pulungan, 2021). Ramdani et al's study showed differences in thinking between boys and girls (Ramdani & Yustiqvar, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%